Block Ownership and Companies' R&D Intensity: The Moderating Effect Of Culture - Aws AlHares; Collins Ntim; David King (Corporate Ownership & Control, 2018)
This study seeks to examine the impact of Block Ownership structure on risk-taking as measured by R&D Intensity in OECD countries. The study uses a panel data of 200 companies from Anglo American and European countries between 2010 and 2014. The ordinary least squares regression is used to examine the relationships. Additionally, to alleviate the concern of potential endogeneity, we use fixed effect regression, two-stage least squares using instrumental variables. The results show that there is a negative and significant relationship between block ownership and risk-taking, with a greater significance among Continental European countries than among Anglo American countries. The rationale for this is that Continental European countries are more likely to have block owners who are also the co-founders and owners of their companies. Also, for the block owners in Anglo American companies, there is greater protection afforded minority shareholders because of the particular legal system in these countries. Future research could investigate risk-taking using other measures, performing interviews with firm's management, investors and owners. This study extends, as well as contributes to the extant CG literature by offering new evidence on the effect of Block ownership on risk-taking between two different traditions. The findings will help regulators and policymakers in the OECD countries in evaluating the adequacy of the current CG reforms to prevent management misconduct and scandals.
Keywords: 330; R&D Intensity; Corporate Governance; Anglo-American Tradition; Continental European Tradition; OECD Countries; Block Ownership